The Effect of Training to the Screening of Tuberculosis Suspected Children by Health Centers Officer - Ã¢Â€Â˜AÃ¯Â¬Âfatussalamah, Rizka; Isfandiari, Muhammad Atoillah (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTChildren are the ones who are at risk of contracting tuberculosis (TB), but so far it has not been a priority. The proportion of tuberculosis in children case detection remains low among all tuberculosis cases. Bojonegoro is one among regencies in East Java which was appointed as the operational trial tuberculin test. The case detection begins with screening of tuberculosis suspects. Screening of tuberculosis suspected children by health centers officer will determine how much the cases of tuberculosis in children are found in health centers. Health officers at the health centers became the most dominant factor in screening of tuberculosis suspected children. Training about tuberculosis in children was done in 16 health centers among 36 health centers in Bojonegoro. This study aimed to analyze the effect of training to the screening of tuberculosis suspected children by health center officers in Bojonegoro. This study is observational analytic with cross-sectional design. The sampling technique is simple random sampling with respondents consisting of 29 doctors and 29 nurses who are responsible for tuberculosis programs in 29 health centers in Bojonegoro. The variables studied were the training and screening of tuberculosis suspected children. The results showed that screening of tuberculosis suspected children was inappropriate from the target (75.9%) and officers who have not attended the training of tuberculosis in children were 58.6%. Logistic regression test showed that there was effect of training to the screening of tuberculosis suspected children (p = 0.019) and prevalence ratio showed that health officers who was attended the training of tuberculosis in children were able to do the screening of tuberculosis suspected children well 8,50 times greater than those who didnât. The training for the officers who have not attended the training of tuberculosis in children needs to be done, so that screening of tuberculosis suspected children in Bojonegoro can be optimally implemented.Keywords: screening, suspected, training, tuberculosis, tuberculosis in children